The pregnancy-associated protein glycodelin as a potential sex-specific target for resistance to immunotherapy in non-small cell lung cancer - Richtmann, Sarah; Marwitz, Sebastian; Muley, Thomas; Koistinen, Hannu; Christopoulos, Petros; Thomas, Michael; Kazdal, Daniel; Allgäuer, Michael; Winter, Hauke; Goldmann, Torsten; Meister, Michael; Klingmüller, Ursula; et al. (Translational research, 2024)
Lung cancer has been shown to be targetable by novel immunotherapies which reactivate the immune system and enable tumor cell killing. However, treatment failure and resistance to these therapies is common. Consideration of sex as a factor influencing therapy resistance is still rare. We hypothesize that the success of the treatment is impaired by the presence of the immunosuppressive pregnancy-associated glycoprotein glycodelin that is expressed in patients with non-small-cell lung cancer (NSCLC). We demonstrate that the glycan pattern of NSCLC-derived glycodelin detected by a lectin-based enrichment assay highly resembles amniotic fluid-derived glycodelin A, which is known to have immunosuppressive properties. NSCLC-derived glycodelin interacts with immune cells in vitro and regulates the expression of genes associated with inflammatory and tumor microenvironment pathways. In tumor microarray samples of patients, high glycodelin staining in tumor areas results in an impaired overall survival of female patients. Moreover, glycodelin colocalizes to tumor infiltrating CD8+ T cells and pro-tumorigenic M2 macrophages. High serum concentrations of glycodelin prior to immunotherapy are associated with a poor progression-free survival (p < 0.001) of female patients receiving PD-(L)1 inhibitors. In summary, our findings suggest that glycodelin not only is a promising immunological biomarker for early identification of female patients that do not benefit from the costly immunotherapy, but also represents a promising immunotherapeutic target in NSCLC to improve therapeutic options in lung cancer.